Narasi Pluralisme Pelaku Aliran Kebatinan Sumarah - Yusuf Ratu Agung; Mohammad Mahpur; Moh Zawawi (Reformed Center for Religion and Society, 2022)
Pluralism as a practice becomes a unique experience, especially in cross-religious encounters. Among those experiences, mysticism had the practice of directly appreciating differences in every moment without causing sensitivity to different faith. This paper aims to present good pluralism practice outside of the formal religion. The research method used a phenomenological qualitative method. The research participants consisted of 7 representatives of the Sumarah community in Malang. Data mining techniques are interviews, focus group discussions, and participant observation. Data analysis used phenomenological thematic categorization technique. The results are first, the pluralism narrative of the Sumarah actors emphasizes the divinity awareness beyond the expression of symbols, dogmas, and religious laws as the prerogative of each religion. Second, Sumarah openly accepts divine awareness as a complete awareness and a reflection of mental pluralism. The implication is that mutually appreciating religious relationships become more meaningful when someone is transformed into enlightenment consciousness.